The appreciation of the jurisdiction of crimes committed during commercial space flights - D. A. Bulgakova; V. A. Bulgakova (Law and Safety)
The author examines the jurisdictional dilemma of determining the appropriate approach to be applied to a crime that could potentially be committed during a space flight with tourists on board by assessing the place of commission of the crime. In addition, the study is based on comparisons under such sources of international law as the Outer Space Treaty (OST) and the Antarctic Treaty (AT). Based on the analysis of certain articles of these documents, the authors propose to regulate commercial space flights by the example of distinguishing the “tourist element”. This approach is based on the fact that Article 8 of the Antarctic Treaty specifically refers to the tourist as a subject of liability and that a person with tourist purposes is protected by national law. Therefore, for the proper international regulation of space tourism and improvement of the Outer Space Treaty, it is recommended to legitimise tourist purposes and to distinguish the status of non-astronaut tourists in order to establish liability for certain criminal acts.